Pengaruh Politik Identitas dalam Kestabilan Ketatanegaraan di Indonesia - Syahdan, Muhammad Saddam (Siyasah, 2024)
Identity politics is a rapidly growing phenomenon in the dynamics of Indonesian politics, where social identities such as religion, ethnicity, and race are used to gain support in elections. This phenomenon has the potential to cause polarization, division, and threats to national unity.This research focuses on analyzing the impact of identity politics on intergroup social relations, as well as how it can threaten national unity and political stability. The research method used is a literature review by analyzing sources such as books, journals, media articles, and regulations related to identity politics. This research also involves interviews with individuals directly involved to understand the impact of identity politics in society. The research results show that excessive identity politics can threaten diversity and exacerbate social tensions. Therefore, it is important to emphasize the values of tolerance and togetherness, and to encourage leaders to focus on vision and ideas rather than group identity.